Consumer Protection against the Marketing of Jangek Cracker Products Not Halal Certified in Terms of Law Number 33 of 2014 Concerning Halal Product Assurance - Rahma, Putri; Irwansyah, Irwansyah (Institut Agama Islam Negeri (IAIN) Curup, 2023)
Purpose: Indonesia is a Muslim-majority country. The state must be able to provide protection to its citizens to carry out religious teachings. One of the obligations of Muslims is to consume halal food/drinks. Consumer Protection Law No. 8/1999 then Law No.Â 33/2014 on Halal Product Assurance is access for Muslim consumers to obtain halal products.Design/Method/Approach: This research is a type of qualitative research that aims to find out how the condition of halal products in the jangek cracker industry and to find out how the Halal Protection Guarantee Law imitates the absence of halal certification in the jangek cracker industry in Medan Deli DistrictFindings: The results of this study show that the products marketed by the industry are true not to have halal certification on the grounds that the manufacturer states that this industry is only a cottage industry that is not required for halal certification. If viewed from the aspect of Law No. 33 of 2014 concerning JPH that the absence of halal certification in the jangek cracker industry in Medan Deli District has violated article 4 of the JPH Law which requires all products marketed to go through halal certification except for products that are derived from haram ingredients, besides that the above problems also result in the loss of consumer rights that have been regulated by law.Originality/Values: The research will provide guarantees for legal protection of Muslim consumer rights against products that are not halal, but also increase the selling value of business actors' products, because consumers will no longer hesitate to buy products traded by business actors.